2008
DOI: 10.1016/j.ahj.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of matrix metalloproteinase 9 and brain natriuretic peptide as clinical biomarkers in chronic heart failure

Abstract: Compared to BNP, MMP-9 is a poor clinical biomarker of remodeling and outcome in patients with systolic heart failure derived from clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
(19 reference statements)
3
21
0
Order By: Relevance
“…The group of 442 ACS patients went on to have 90 end point events, and follow-up measurements were based on 51 events in 338 patients, which represents a relatively low power for the study and we cannot discount the possibility of type II errors. Nevertheless, our results on baseline associations of adiponectin with age and the female gender [36], as well as with BNP [10][11][12][13][14][15][17][18][19], and the link to end points [19,23,37], is consistent with the literature and suggest the results are externally valid. Further larger studies with serial measurements are required to confirm and expand on the potential mechanistic relationships of adiponectin, BNP and cardiac stress.…”
Section: Discussionsupporting
confidence: 93%
“…The group of 442 ACS patients went on to have 90 end point events, and follow-up measurements were based on 51 events in 338 patients, which represents a relatively low power for the study and we cannot discount the possibility of type II errors. Nevertheless, our results on baseline associations of adiponectin with age and the female gender [36], as well as with BNP [10][11][12][13][14][15][17][18][19], and the link to end points [19,23,37], is consistent with the literature and suggest the results are externally valid. Further larger studies with serial measurements are required to confirm and expand on the potential mechanistic relationships of adiponectin, BNP and cardiac stress.…”
Section: Discussionsupporting
confidence: 93%
“…Recent community based studies demonstrated an approximately 2-fold increased risk of hypertension progression in subjects with elevated MMP-9 levels. 46-49 Moreover, these elevated MMP-9 plasma levels were associated with higher PIIINP levels. In the present study, both PIIINP and MMP-9 were important components of the multi-biomarker prediction modeling for LVH.…”
Section: Discussionmentioning
confidence: 93%
“…55-57 The biomarkers measured in the present study fulfill this requirement. In addition, it is clear that no single biomarker is optimal for screening, diagnosis and potentially disease management and therefore the multivariable modeling utilized in the present study addressed this issue 23,38,40,47-49,55-57 . Finally, the current study clearly fulfilled the recommended first “phase of evaluation” outlined by the AHA.…”
Section: Discussionmentioning
confidence: 99%
“…(Creemers et al 2001; Wilson et al 2002; Sundstrom et al 2004; Wagner et al 2006; Yan et al 2006; Moe et al 2008; Zhao et al 2009; Buralli et al 2010; Dini et al 2010; Yang et al 2010). However, recent studies have found no significant association between plasma levels of MMP-9 and increased risk for myocardial infarction as well as other forms of heart failure (Vorovich et al 2008; Welsh et al 2008; Eldrup et al 2012). The apparent difference could be due to variations in the study population and (or) gene polymorphisms (Mizon-Gerard et al 2004; Shevchenko et al 2010).…”
Section: Mitochondria In Heart Diseasementioning
confidence: 96%